"This shame, it is everywhere": Cross-generational menstruation experiences among women living in Florence, Italy - Anna G. Trieloff; Elizabeth H. Salwitz; Sofia Hrubiak; Sophia P. Patel; Mackenzie Greulach; Shannon Hoffman; Alexandra T. Hughes-Wegner; Andrea L. DeMaria (New Prairie Press, 2024)
Menstruation is a worldwide biological phenomenon that can have differing impacts based on what women were taught by their family members and friends. The purpose of this investigation was to understand menstruation experiences and communication, from menarche through menopause, among a sample of cross-generational women living in Florence, Italy. In-depth interviews (n=28) were conducted in English in May and June 2022 to investigate different aspects affecting menstruation throughout a woman's lifetime. Most participants reported having received limited preparation for menarche, menstruation, and menopause. Education typically came from the participants' mothers rather than school, which can be attributed to the culture and religion ingrained within Italian society. and menstrual health is still seen as a taboo by older generations. However, discussing these topics with friends and family is becoming more common among younger generations. Results indicated Italian women's experiences surrounding menarche, menstruation, and menopause, including preparation, education, and openness and discussion. Findings revealed the changing perceptions and generational differences within Italian culture regarding women's menstruation. This will allow educators, healthcare providers, and families to better understand what education is currently being provided and where more is needed.